DAYA TARIK WISATA PANTAI CAROLINA KOTA PADANG - Putra, Dion Rahmana; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
The purpose of this research is to know the travelers opinion at as seen from four indicators: attraction, accesibilities, amanities, and ancillary services. The type of research is descriptive with the data qualitative and quantitative. Technique data collection was carried out by using the method interview, observation, documentation, and quetioner. The research is using purposive sampling and snowball sampling, involving informants wich are: five people from management, eight people from community, and seventy one tourist who come to visit. Technique data collection conducted by interviewing managers and the community, and spreading quetioner by using scale likert that are highly capable validity and reliability, and sought the percrentage level of achievement of repondents with the help of computer program SPSS version 16.00. Technique analysis data used in this research was reduction data, presentation of data, the conclusion, and calculation the level of achievement respondents. The result of this research found the overall tourist attraction of Carolina coastal is not good enough, and einforced also by tourist questionnaires that showed less good results about Carolina coastal tourist attraction by 46 %.Keywords: Tourist attraction, Tourism1Prodi